Drug Repurposing of FDA Compounds against ff-Glucosidase for the Treatment of Type 2 Diabetes: Insights from Molecular Docking and Molecular Dynamics Simulations - Rashid, Rebwar Saeed M.; Temurlu, Selin; Abourajab, Arwa; Karsili, Pelin; Dinleyici, Meltem; Al-Khateeb, Basma; Icil, Huriye (Mdpi, 2023)
Type 2 diabetes mellitus is a chronic health problem that can be controlled by slowing one's carbohydrate metabolism by inhibiting alpha-glucosidase, an enzyme responsible for carbohydrate degradation. Currently, drugs for type 2 diabetes have limitations in terms of safety, efficiency, and potency, while cases are rapidly increasing. For this reason, the study planned and moved towards drug repurposing by utilizing food and drug administration (FDA)-approved drugs against ff-glucosidase, and investigated the molecular mechanisms. The target protein was refined and optimized by introducing missing residues, and minimized to remove clashes to find the potential inhibitor against ff-glucosidase. The most active compounds were selected after the docking study to generate a pharmacophore query for the virtual screening of FDA-approved drug molecules based on shape similarity. The analysis was performed using Autodock Vina (ADV)-based on binding affinities ( -8.8 kcal/mol and 8.6 kcal/mol) and root-mean-square-deviation (RMSD) values (0.4 angstrom and 0.6 angstrom). Two of the most potent lead compounds were selected for a molecular dynamics (MD) simulation to determine the stability and specific interactions between receptor and ligand. The docking score, RMSD values, pharmacophore studies, and MD simulations revealed that two compounds, namely Trabectedin (ZINC000150338708) and Demeclocycline (ZINC000100036924), are potential inhibitors for ff-glucosidase compared to standard inhibitors. These predictions showed that the FDA-approved molecules Trabectedin and Demeclocycline are potential suitable candidates for repurposing against type 2 diabetes. The in vitro studies showed that trabectedin was significantly effective with an IC50 of 1.263 +/- 0.7 mu M. Further investigation in the laboratory is needed to justify the safety of the drug to be used in vivo.
Keywords: drug repurposing; diabetic mellitus; alpha-glucosidase; molecular docking